Modelagem matemática e Geogebra na educação básica: um estudo a partir de dissertações do PROFMAT - RAMOS, Regilene de Oliveira (2023)
The present work aims to analyze pre-selected dissertations from the database of the Professional Master's Degree in Mathematics in National Network (PROFMAT) and understand how Mathematical Modeling and Geogebra can contribute to teaching and consequently the learning of mathematics in basic education. The research is of a qualitative nature and presents a research method called State of the Art which fits as a bibliographic research. After filtering the database, we focused on the analysis of 12 PROFMAT dissertations. It was found that mathematical modeling and Geogebra open new paths for teaching mathematics, allow the teacher to work with content more easily and with new perspectives and allows students to understand concepts that would seem complicated and still allows students to analyze the mathematics present in real everyday situations, making the teaching and learning of mathematics more engaging and meaningful.